Thermo and Photoresponsive Emulgel Loaded with Copaifera reticulata Ducke and Chlorophylls: Rheological, Mechanical, Photodynamic and Drug Delivery Properties in Human Skin - Katieli da Silva Souza Campanholi; Ranulfo Combuca da Silva Junior; Jonas Marcelo Jaski; Jéssica Bassi da Silva; Mariana Carla de Oliveira; Rafaela Said dos Santos; Magali Soares dos Santos Pozza; Lidiane Vizioli de Castro-Hoshino; Mauro Luciano Baesso; Lucio Cardozo-Filho; Marcos Luciano Bruschi; Wilker Caetano (MDPI AG, 2022)
Recently, the number of new cases of cutaneous leishmaniasis has been of concern among health agencies. Research that offers new therapeutic alternatives is advantageous, especially those that develop innovative drugs. Therefore, this paper presents the incorporation of Copaifera reticulata Ducke and chlorophyll extract into Pluronic®® F127 and Carbopol gels, under optimized polymer quantities. The chlorophyll extract (rich in photosensitizing compounds) was obtained by continuous-flow pressurized liquid extraction (PLE), a clean, environmentally friendly method. The system aims to act as as a leishmanicidal, cicatrizant, and antibiotic agent, with reinforcement of the photodynamic therapy (PDT) action. Rheological and mechanical analyses, permeation studies and bioadhesiveness analyses on human skin, and PDT-mediated activation of Staphylococcus aureus were performed. The emulgels showed gelation between 13° and 15 °C, besides pseudoplastic and viscoelastic properties. Furthermore, the systems showed transdermal potential, by releasing chlorophylls and C. reticulata Ducke into the deep layers of human skin, with good bioadhesive performance. The application of PDT reduced three logarithmic colony-forming units of S. aureus bacteria. The results support the potential of the natural drug for future clinical trials in treating wounds and cutaneous leishmania.